2023
DOI: 10.1002/adma.202208029
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Carbon Using Commodity Polypropylene

Abstract: focused on research and product development of carbon-based materials, exemplified by the discoveries of fullerene, [10] carbon nanotubes [11] and graphene, [12] as well as fabrication of porous carbon [13] and carbon black additives for many commercial applications. [14] However, most industries can only employ these functional carbon materials as fillers, necessitating additional components, often polymer matrices, for imparting processability. [15,16] The presence of matrix materials can greatly diminish ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Notably, sulfonation induced crosslinking in polyolefin systems has been demonstrated as a diffusion-controlled reaction. [29][30][31] Herein, by including unsaturated bonds in the precursor design of the amorphous polyolefin-containing systems (Fig. S1 †), it is found that the required crosslinking time can be significantly reduced from 4 h (for SEBS) to 20 min (for SBS), corresponding to nearly 8-fold enhancement in reaction kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, sulfonation induced crosslinking in polyolefin systems has been demonstrated as a diffusion-controlled reaction. [29][30][31] Herein, by including unsaturated bonds in the precursor design of the amorphous polyolefin-containing systems (Fig. S1 †), it is found that the required crosslinking time can be significantly reduced from 4 h (for SEBS) to 20 min (for SBS), corresponding to nearly 8-fold enhancement in reaction kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…The 145 °C reaction condition approaches a plateau after reaction for 4 h at a value of 48%, which increases slightly to 52% after reaction for 8 h; these mass gain values are similar to those of other studies using polypropylene as a carbon precursor. 43,44 It is worth noting that extension of the reaction at 145 °C to 12 h results in a slightly decreased value for both mass gain and gel fraction. It is observed that this sample breaks down into very fine powders after reaction (Figure S3), suggesting that the decreased mass gain and gel fraction are potentially due to significant degradation/scission of the polymer chains becoming prevalent at long reaction times suggesting oversulfonation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the sulfonation reaction introduces sulfonic acid groups which impart hydrophilicity to the PP backbone, facilitating acid penetration to further promote crosslinking. As a comparison, a previous study investigated the use of PP‐based filaments to prepare 3D structured carbon, [ 51 ] through similar sulfonation‐based crosslinking and carbonization approach. Investigation of the 3D printed structure's morphology after crosslinking revealed the formation of micron‐sized cracks which promoted diffusion of sulfuric acid throughout the structure and subsequently accelerate reaction kinetics.…”
Section: Resultsmentioning
confidence: 99%